Penerapan Metode Field trip pada MK. Pendidikan Lingkungan Hidup untuk Meningkatkan Kepedulian Mahasiswa terhadap Permasalahan Sampah - Bayu Widiyanto (Universitas Pancasakti Tegal, 2017)
One way to develop human awareness of the environment is by applying field trip method on learning. This study aimed to examine the effectiveness of field trip (observation of waste management in the field) approach to develop learning outcomes of waste chapters and students' awareness of the environment. Field trip method is a method of learning outside the classroom, where students is invited to visit a location. By visiting the location directly related to the subject matter, students are expected to be more understand and get a real picture of the material being studied. This research used pretest-posttest control design. The sample of this research was students of Science Education of Teacher Trainning Education Faculty of UPS Tegal who took environmental education subject. Data collection techniques used unstructured interviews, documentation, reports and tests. The results showed that student learning outcomes increased proved by classical completeness from 76% to 88% after field trip method being implemented Therefore it is expected that field trip method becomes one of the reference for teacher in creating learning science field especially on Environmental Education subject (PLH).